A Laryngoscope with Shape Memory Actuation - Fischer, Nikola; Ho, Patty; Marzi, Christian; Schuler, Patrick; Mathis-Ullrich, Franziska (Current Directions in Biomedical Engineering, 2024)
Endotracheal intubation is a medical procedure to secure a patient's airways, which can be challenging in emergency situations due to an individual's anatomy. Intubation blades can benefit from an adjustable design with shape memory alloys. We present a novel blade design with two degrees of freedom, continuously transforming a straight into a curved blade. Our demonstrators reached mean angular deflections up to 16 ° without exceeding outer blade temperatures of 40 ° C. Mean forces of almost 24N were applicable. This approach has the potential to reduce the complexity of intubation procedures and increase the success rate, especially in time-critical emergency situations.
CRIS-Team Scopus Importer:2024-09-20
Keywords: endotracheal intubation; ETI; nickel-titanium; SMA; smart materials